Evaluasi Kerusakan Tegakan Tinggal Akibat Pemanenan Menggunakan Landsat 7 ETM+ di HPH PT Sari Buana Dumai Provinsi Riau - Susilawati; Jaya, I Nengah Surati (Institut Pertanian Bogor (IPB University), 2003)
This paper describes the use of Landsat 7 ETM+ for evaluating logged over stand condition. The digital classification and spatial analysis were performed to identity degree of stand damage and their spatial distribution. The study found that Landsat 7 ETM+ images were powerful to identify logged over stand damage having Kappa and overall accuracies more than 99%, as well as interclass separability more than 1900 (good). There is also a spatial relationship between the stand damage and distance from the logging road.